2015
DOI: 10.1155/2015/737621
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced Signaling Pathways Contribute to Intestinal Metaplasia and Gastric Carcinogenesis

Abstract: Helicobacter pylori (H. pylori) induces chronic gastric inflammation, atrophic gastritis, intestinal metaplasia, and cancer. Although the risk of gastric cancer increases exponentially with the extent of atrophic gastritis, the precise mechanisms of gastric carcinogenesis have not been fully elucidated. H. pylori induces genetic and epigenetic changes in gastric epithelial cells through activating intracellular signaling pathways in a cagPAI-dependent manner. H. pylori eventually induces gastric cancer with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 89 publications
2
43
0
Order By: Relevance
“…Previously, numerous oncogenic signaling pathways, including the PI3 kinase‐AKT, β‐catenin‐WNT, Hedgehog/GLI, ERK‐MAPK, JNK, and NF‐κB pathways, have been studied and demonstrated to be involved in H. pylori pathogenesis . In this study, we confirmed that some of those signaling pathways are involved in H. pylori ‐associated gastric cancer, such as focal adhesion, Th1 and Th2 cell differentiation, Th17 cell differentiation, bacterial invasion of epithelial cells, epithelial cell signaling, and the NF‐κB and Hedgehog signaling pathways.…”
Section: Discussionsupporting
confidence: 80%
“…Previously, numerous oncogenic signaling pathways, including the PI3 kinase‐AKT, β‐catenin‐WNT, Hedgehog/GLI, ERK‐MAPK, JNK, and NF‐κB pathways, have been studied and demonstrated to be involved in H. pylori pathogenesis . In this study, we confirmed that some of those signaling pathways are involved in H. pylori ‐associated gastric cancer, such as focal adhesion, Th1 and Th2 cell differentiation, Th17 cell differentiation, bacterial invasion of epithelial cells, epithelial cell signaling, and the NF‐κB and Hedgehog signaling pathways.…”
Section: Discussionsupporting
confidence: 80%
“…Despite a declining rate of GC over the past decades, the 5‐year survival rate of GC patients is <20% . Moreover, no less than two‐thirds of GC occurs in developing countries, and China has the most GC patients in the world . Despite significant medical progress and efforts in promoting the survival of GC patients, the basic molecular mechanisms of the GC are until recently still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The turning point of the malignant tissue/cell changes is in the status of intestinal metaplasia [20]. While many factors are involved in the progression of GC, aberrant expression of epidermal growth factor receptor (EGFR) and its cognate ligands (e.g.…”
Section: Discussionmentioning
confidence: 99%